Employment and training of ICT specialist in EU and Bulgaria enterprises - Stefanova, Tereza (Yearbook Telecommunications, 2017)
The article shows the trends in the recruitment of ICT specialists in EU countries and in Bulgaria, as well as the training provided by enterprises. Statistical surveys have been carried out on EU businesses that recruit and encounter difficulties in filling vacancies for ICT and economic professionals. In addition to recruiting qualified ICT professionals and employees with professional skills, some enterprises provide ICT training for both professionals and ICT consumer skills. The article presents the change in the number of active enterprises, employees and employees; number of non-financial enterprises by groups according to the number of persons employed in them for economic activity in the Information and Communication area in Bulgaria according to NSI data. It can be concluded that businesses in all EU countries have difficulties in recruiting ICT specialists. EU businesses provide training to upgrade the skills of ICT professionals, but also other staff to develop their ICT skills. In conclusion, the areas of realization of the graduates of the Bachelor and Master programs of the Department of Telecommunications at NBU are presented.